FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEMATIAN BAYI BERAT LAHIR RENDAH DI RSUD LABUANG BAJI MAKASSAR - Ny. Daswati; Nurbiah Eka Susanty (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2017)
Low Birth Weight (LBW is defined as a neonate born too small, a baby born with a weight between 500- <2500 grams. Objective: To find out factors related to mortality of low birth weight babies at Labuang Baji Regional General Hospital of Makassar.This research method uses analytic observation with cross sectional study approach. The population in this study were all low birth weight infants (BBLR) treated at the Regional General Hospital of Labuang Baji Makassar in 2013-2015. The sample in this study were all low birth weight babies who died at the Regional General Hospital of Labuang Baji Makassar in 2013-2015. Sampling technique purposive sampling.Conclusion: There is a significant association between asphyxia, infection/ sepsis, hypoglycemia, hyperbilirubinemia, hypothermia, Respiratory Distress Syndrome (RDS) on the occurrence of LBW death.Suggestion: The need for early detection of complications that may occur in infants with LBW. Appropriate and fast handling, including referral systems for babies with LBW. Keywords : Neonatus, Died, Low Birth Weight